The Evaluation of Thyromental Height Test as a Single, Accurate Predictor of Difficult Laryngoscopy - Rawal, Prabhat; Shrestha, Surendra Man (Journal of Nepal Health Research Council, 2020)
Background: Thyromental Height Test is a relatively new, easy method considered as a more accurate predictor of difficult laryngoscopy than existing methods. The aim of this study was to evaluate its accuracy in predicting difficult laryngoscopy as compared to commonly used methods. Methods: This hospital based, cross-sectional, observational study was conducted on 246 patients scheduled for surgery under general anesthesia with endotracheal intubation. Airway assessment was done during pre-anesthetic assessment by Thyromental Height Test, Modified Mallampati Test, Thyromental Distance and Sternomental Distance measurements and predicted as ‘difficult’ or ‘easy’ laryngoscopy based on accepted cut-off values. Direct laryngoscopic view was assessed after administration of general anesthesia by a laryngoscopist unaware of the pre-anesthetic assessments and recorded as ‘actual’ difficult or easy laryngoscopy based on Cormack-Lehane grades. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of each clinical test were determined. Results: Thyromental Height Test had the highest sensitivity (71.42%) and negative predictive value (98.9% respectively) but lowest accuracy (77.2%). Maximum specificity was observed with Thyromental Distance and Sternomental Distance (97.49% each). Thyromental Distance had the highest positive predictive value (25%) and accuracy (95.52%). Conclusions: Thyromental Height Test, with its high sensitivity, is a useful predictor of difficult laryngoscopy. However, due a high number of false positives and relatively low accuracy, it cannot be considered as a sole, reliable and accurate predictor of difficult laryngoscopy. Keywords: Accuracy; difficult laryngoscopy; predictor; thyromental height